On the error probability of convolutionally encoded spread spectrumBPSK in frequency selective Rayleigh fading - Al-Semari, S.A. (1998)
An exact expression for the pairwise error probability of convolutionally encoded spread spectrum BPSK with ideal interleaving and RAKE reception over frequency selective Rayleigh fading channels is presented. This expression is used to find a tight upper bound on the bit error probability using the transfer function approach